2007
DOI: 10.1016/j.neuron.2007.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory Role of NR2A for Metaplasticity in Visual Cortex

Abstract: Light deprivation lowers the threshold for long-term depression (LTD) and long-term potentiation (LTP) in visual cortex by a process termed metaplasticity, but the mechanism is unknown. The decreased LTD/P threshold correlates with a decrease in the ratio of NR2A to NR2B subunits of cortical NMDA receptors (NMDARs) and a slowing of NMDAR-mediated excitatory postsynaptic currents (EPSCs). However, whether and how changes in NR2 subunit expression contribute to LTD and LTP have been controversial. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
167
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(184 citation statements)
references
References 61 publications
13
167
0
1
Order By: Relevance
“…Given the lack of an effective pharmacological tool to explore the role of the NR2A subunit (see Berberich et al, 2005;Weitlauf et al, 2005;Frizelle et al, 2006;Neyton and Paoletti, 2006;Kash and Winder, 2007), we utilized NR2A KO mice to determine the functional synaptic presence of the NR2A subunit in the vBNST. While NMDA-EPSCs were still readily elicited in vBNST neurons from NR2A KO mice, there was a significant alteration in the kinetics of the response ( Figures 3a-c), consistent with what has been demonstrated in other brain regions (Fu et al, 2005;Lu et al, 2006;Philpot et al, 2007). Both the decay time (294747 ms for the NR2A KO, n ¼ 12; 128720 ms for the wild type, n ¼ 10; po0.01; Figure 3b) and the rise time (1171 ms for the NR2A KO, n ¼ 12; 6.670.3 ms for the wild type, n ¼ 10; po0.01; Figure 3c) were significantly slower when compared to wild-type animals.…”
Section: Nr2a and Nr2b Subunits Contribute To Synaptic Nmdars In The supporting
confidence: 87%
“…Given the lack of an effective pharmacological tool to explore the role of the NR2A subunit (see Berberich et al, 2005;Weitlauf et al, 2005;Frizelle et al, 2006;Neyton and Paoletti, 2006;Kash and Winder, 2007), we utilized NR2A KO mice to determine the functional synaptic presence of the NR2A subunit in the vBNST. While NMDA-EPSCs were still readily elicited in vBNST neurons from NR2A KO mice, there was a significant alteration in the kinetics of the response ( Figures 3a-c), consistent with what has been demonstrated in other brain regions (Fu et al, 2005;Lu et al, 2006;Philpot et al, 2007). Both the decay time (294747 ms for the NR2A KO, n ¼ 12; 128720 ms for the wild type, n ¼ 10; po0.01; Figure 3b) and the rise time (1171 ms for the NR2A KO, n ¼ 12; 6.670.3 ms for the wild type, n ¼ 10; po0.01; Figure 3c) were significantly slower when compared to wild-type animals.…”
Section: Nr2a and Nr2b Subunits Contribute To Synaptic Nmdars In The supporting
confidence: 87%
“…The coincident alterations in the NR2A/NR2B ratio and in the LTP/LTD inspired the assumption that changes in NR2A/NR2B lead to sliding of LTP/LTD (Bear, 1995;Quinlan et al, 1999a,b;Philpot et al, 2007;Yashiro and Philpot, 2008). They put forward a hypothesis that activitydependent changes in NR2A/NR2B are involved in metaplastic regulation of the LTP/LTD threshold (Morishita et al, 2007;Yashiro and Philpot, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A series of elegant investigations by Bear's laboratory in layer 3 of the visual cortex demonstrated that the "sliding threshold" is an attractive mechanism based on experience-dependent alterations in NMDARs (Kirkwood et al, 1996;Quinlan et al, 1999a,b;Philpot et al, 2001Philpot et al, , 2003Philpot et al, , 2007Shouval et al, 2002;Bear, 2003;Iny et al, 2006). The coincident alterations in the NR2A/NR2B ratio and in the LTP/LTD inspired the assumption that changes in NR2A/NR2B lead to sliding of LTP/LTD (Bear, 1995;Quinlan et al, 1999a,b;Philpot et al, 2007;Yashiro and Philpot, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now understood that the qualities of cortical synaptic plasticity depend on the recent history of cortical activity, a property called metaplasticity (23). After a period of attenuated cortical activity, the threshold for synaptic potentiation is reduced (24)(25)(26). Thus, the period of quiescence that immediately follows initiation of reverse occlusion lowers the threshold for synaptic potentiation, enabling subsequent visual experience to increase synaptic effectiveness when it would have otherwise been without effect (27).…”
mentioning
confidence: 99%